Uji Fitokimia Dan Toksisitas Ekstrak Kasar Gastropoda (Telescopium telescopium) Terhadap Larva Artemia salina - Putri, Mukti K. Diana; Pringgenies, Delianis; Radjasa, Ocky Karna (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Gastropod is one of the marine organisms that can be used as a source of natural bioactive compounds, one of which is Telescopium telescopium. T. telescopium until now it has not been yet exploited optimally, some people still use it as feed ingredients that contain high protein nutrition, however it must be supported by scientific information about the efficacy and side effects. This research aims at determining the secondary metabolite by crude extract T. telescopium, and the lethal toxicity value (LC50-24 hours). The research consisted of two steps, namely the phytochemical and toxicity test. The method used exploratif and experimental laboratory with a complete randomized design, which consited of five concentration treatments namely 25.12, 63.1, 158.5, 398.15, and 1000 ppm with three replications. Each treatment used 10 Artemia salina larvae, and observations were made during 24 hours of Artemia salina larvae mortality. LC50 was determined by probit analysis using the EPA Probit Analysis Program Version 1.5 Finney. The results of the phytochemical test showed that crude extract T. telescopium contain alkaloid compounds, steroids, flavonoids. The results BSLT (Brine Shrimp Lethality Test) of crude extract T. telescopium LC50-24 hours showed that the crude extract clorofom (229.562 ppm), crude extract ethyl acetate (244.906 ppm), and crude extract methanol (197.242 ppm). LC50-24 hours < 1000 ppm showed that the crude extract Telescopium telescopium potent antitumor compounds.